Stimulasi Perkembangan Karakter dan Kemandirian Anak Usia Dini Melalui Kegiatan Entrepreneurship di TK Adni Islamic School Surabaya - Mei Ariani Kusumawati; Nurul Khotimah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
Stimulating Character Development and Independence in Early Childhood Through Entrepreneurship Activities at ADNI Islamic School Surabaya Kindergarten discusses the implementation of stimulating character development and independence in early childhood through Entrepreneurship activities at ADNI Islamic School Kindergarten Surabaya. This Entrepreneurship activity aims to stimulate positive character development and increase children's independence from an early age. By exploring business concepts practically, children are invited to develop creativity, critical thinking, perseverance and collaborate with each other. This research illustrates how the ADNI Islamic School Surabaya Kindergarten integrates the principles of Entrepreneurship into the curriculum, providing a learning experience that is more than just theory. Interactive and inclusive learning methods help children understand business values, responsibility and teamwork. The results of this program are expected to create children who not only have practical knowledge in business, but also foster positive attitudes, such as courage, perseverance, never giving up, and a responsible attitude. By utilizing Entrepreneurship activities as a means of stimulating character development and independence, research This notes the positive impact of this program on the formation of children's independent personalities. Analysis of research results and observations presents a clear picture of how these activities respond to the developmental needs of early childhood. Therefore, this research provides valuable insights for educators, parents and educational practitioners who are interested in developing comprehensive and relevant educational models to shape children's character and independence from an early age.